Polyaniline as Photocatalytic Promoter in Black Anatase TiO2. (December 2017) - Kavil, Jithesh; Ullattil, Sanjay Gopal; Alshahrie, Ahmed; Periyat, Pradeepan
Graphical abstract: Highlights: Polyaniline-Black Anatase Titania (PANI-BAT) composite has been synthesised by a modified hydrothermal method. Light absorption capability was enhanced and photo corrosivity was inhibited considerably when BAT was incorporated into the PANI matrix via in situ polymerization. This hybrid material has shown excellent photocatalytic activity under visible light. Abstract: The effect of conducting polymer matrix, polyaniline (PANI) on the photocorrosion and photochemical activities of Black Anatase Titania (BAT) has been systematically investigated. PANI-BAT composite has been fabricated by a modified hydrothermal method and successive in situ polymerization of aniline. This hybrid material has shown excellent photo catalytic activity than BAT under visible light. The rate constant value of dye degradation in presence of the PANI-BAT composite was found 2.4 × 10 −2  min −1, which is 1.5 times greater than that of the commercially available photocatalyst Degussa P25 and BAT. The study unveils the strong correlation between electrochemical impedance measurements and the photochemical results.